2017
DOI: 10.1016/j.enpol.2017.05.036
|View full text |Cite
|
Sign up to set email alerts
|

How to achieve full electrification: Lessons from Latin America

Abstract: Electricity coverage in Latin America has increased substantially in recent decades, rising from 50% of the population in 1970 to more than 95% in 2015. Growth, however, slowed in the 1990s as many countries experienced difficulties in extending their networks further, in particular to serve those living in isolated and rural areas. In spite of this, the process of electrification was not interrupted and at the beginning of the 2010s decade most countries in the region were able to provide access to electricit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 84 publications
(76 reference statements)
0
25
0
1
Order By: Relevance
“…Urban regions have significantly higher access rates to modern fuels than rural regions (e.g., in sub‐Saharan Africa 42% of urban compared to 5% of rural residents have access) and show a higher likelihood of sustained use (Alem et al, ; McLean et al, ; Puzzolo & Pope, ). The establishment of electricity and LPG distribution systems in urban areas is easier because the population is more affluent and high population density reduces per capita connection cost (Banal‐Estañol, Calzada, & Jordana, ; Bhide & Monroy, ; Coelho, Sanches‐Pereira, Tudeschini, & Goldemberg, ). Studies at the household level suggest that households tend to adopt an energy portfolio (energy stacking), and the linear progression proposed by the energy ladder is often interrupted by other factors (Hiemstra‐van der Horst & Hovorka, ; van der Kroon, Brouwer, & Van Beukering, ) as shown below.…”
Section: Energy Access: Household Cooking Fuel Transitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Urban regions have significantly higher access rates to modern fuels than rural regions (e.g., in sub‐Saharan Africa 42% of urban compared to 5% of rural residents have access) and show a higher likelihood of sustained use (Alem et al, ; McLean et al, ; Puzzolo & Pope, ). The establishment of electricity and LPG distribution systems in urban areas is easier because the population is more affluent and high population density reduces per capita connection cost (Banal‐Estañol, Calzada, & Jordana, ; Bhide & Monroy, ; Coelho, Sanches‐Pereira, Tudeschini, & Goldemberg, ). Studies at the household level suggest that households tend to adopt an energy portfolio (energy stacking), and the linear progression proposed by the energy ladder is often interrupted by other factors (Hiemstra‐van der Horst & Hovorka, ; van der Kroon, Brouwer, & Van Beukering, ) as shown below.…”
Section: Energy Access: Household Cooking Fuel Transitionmentioning
confidence: 99%
“…Households consider access to and reliability of the supply of modern fuels when making their cooking fuel transition decision (Groh, Pachauri, & Narasimha, ). Unstable or infrequent supply requires households to rely on multiple fuels including firewood; reliability concerns decrease the initial adoption likelihood of advanced fuels and cookstoves (Banal‐Estañol et al, ; Ding et al, ; Malla & Timilsina, ). An interview‐based study of 78 households in Maun, Botswana revealed that households, regardless of wealth, rely on multiple energy sources (dominantly firewood) to mitigate price and supply fluctuations (Hiemstra‐van der Horst & Hovorka, ).…”
Section: Energy Access: Household Cooking Fuel Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing energy access is a challenge when there are drastic differences between energy use in urban and rural areas [3,4]. This, together with low incomes of the rural population, geographic conditions, unsuitable policies design, deficient institutional frameworks, and limited financial options [5,6], demand innovative ways to overcome the current weaknesses of rural electrification. As much as…”
Section: Introductionmentioning
confidence: 99%
“…8 Previous studies (e.g. Banal-Estañol et al, 2017;McRae and Wolak, 2019;Winkler et al, 2011) looked at the main policies adopted in different regions, including Latin American countries. They assessed different aspects of the problem including energy coverage, clean energy penetration, affordability, and reliability.…”
Section: Introductionmentioning
confidence: 99%